Proposição formativa de professores a partir da reflexão crítica de objetos virtuais de aprendizagem - (:unkn) unknown (Universidade Estadual de Goiás, 2016)
Teacher training can be studied under different aspects and on many fronts. In this sense, this research discusses issues related to the possible formative contributions development analysis of Virtual Learning Objects (OVAs) and production of a didactic sequence that encompasses this theme in a perspective of training reflective crítical teachers. This research was developed under a qualitative perspective guided by the documentary research in OVAs contained on the teacher's website, having been founded on the concepts of Historical-Crítical Pedagogy and Health approaches. Published surveys have shown a still unexplored field in research with OVAs that are the analyzes beyond their subject content or technical elements, the results also indicated the need to consider proposals that not only instrumentalize the teacher in the use of resources but enable thinking its application for a training that includes political, cultural, historical aspects etc. On how analyze OVAs, it was made an analysis matrix that reached pedagogical aspects and enable understanding of what pedagogical concepts and health they approach. In the second part of the research we formulated a training proposition for teachers from the perspective of Historical-Crítical Pedagogy, so that theoretical and practical weaknesses detected in literature surveys and analyzes of OVAs could be met. The results make it evident that the process of analysis of teaching resources can support teachers’ training in the historical crítical perspective pedagogy, since this action is inserted in a formative proposal consistent with this theory, and that is not held in isolation , ahistorical, a-crítical and without defined pedagogical objectification.
Keywords: Pedagogia histórico-crítica; Análise de OVA; Formação de professores; Tendências pedagógicas; Possibilidades didático-pedagógica; historical-crítical pedagogy; OVA analysis; Teacher training; Health approaches; Didactic and pedagogical possibilities; CIENCIAS HUMANAS::EDUCACAO